The Effectiveness of Stingless Bees on Pollination of Bitter Melon Plants Momordica charantia L. (Cucurbitaceae) - Andi Gita Maulidyah Indraswari Suhri; RC Hidayat Soesilohadi; Ramadhani Eka Putra; Rika Raffiudin; Hery Purnobasuki; Ali Agus; Sih Kahono (Universitas Gadjah Mada, 2022)
This study aimed to measure the effectiveness of stingless bee Tetragonula cf. biroi pollination on the fruit formation of bitter melon Momordica charantia plants. We used hoods on the observed bitter melon plants. In the first hood, stingless bees are inserted to help pollinate 100 bitter melon plants, while in the other hoods, stingless bees are not inserted so that there is no assistance in pollinating the other 100 bitter melon plants. The method used is the focal sampling method for 25 days of observation. Based on the results of the study, stingless bee pollination assistance increased the percentage of the number of flowers that became fruit by 390%, the weight of seeds/fruit by 64%, number of seeds/fruit by 260%, fruit weight by 163%, fruit diameter by 91%, and fruit length by 86%. In addition to the size of the fruit, the shape of the bitter melon pollinated by bees is standard (long and straight). In contrast, the bitter melon that does not get pollination assistance grows with a bent shape resembling the letter